A simulation study of lubricating oil pump for an aero engine/ Tarique Hussain [et al.] - Hussain, Tarique; Sarangi, Niranjan; Sivaramakrishna, M.; Kumar, M. Udaya (Universiti Teknologi MARA, 2021)
The lubrication system of an aeroengine is intended to lubricate and cool bearings, gears, and splines to ensure a high level of safety and reliability for many operating hours of an aircraft. One of the important accessories of the lubrication system of an aeroengine is the oil pump which consists of multiple pumps with tandem gerotor elements housed in a single casing. The lubrication pump consists of multi positive displacement pumps of "GEROTOR" type, driven by a single shaft. The aim of this paper is to study the influence of altitude conditions on the pump performance and develops a simulation technique for the prediction of output flow rate at various on and off-design conditions. A numerical study has been conducted using commercial CFD code ANSYS-Fluent. Volumetric efficiency is considered as the main parameter for the evaluation of pump performance at various operating conditions. Further, the experimental study has been carried out by simulating low inlet pressure conditions at the inlet of the pump. The comparison between simulation and experimental results shows that results are matching within a 6% deviation. Thus, the simulation method is appropriate for predicting the altitude performance of gerotor pump used in the lubrication system of an aero engine. The study concludes that the contribution of inlet pressure to the pump performance is significant.